Molecular Cloning of Phytase Gene from Bacillus subtilis NCIM-2712 - Singh Rajput, Megha Kadam Bedekar, Sunil Kumar, Iti Gontia and Sharad Tiwari, Sunil Yadav, Keerti Tantwai*, Lalit (Journal of Phytology, 2011)
Phytases are enzymes which hydrolyze phytate. Bacillus species are known to produce a thermostable phytase. The Bacillus subtilis strain NCIM-2712 was chosen for cloning of phy gene. Primers were designed for phy gene amplification using the phy gene sequence of B. subtilis (AF298179). A sequence of 1059 bp characteristic of phy gene was obtained on PCR amplification. This gene was cloned into InsT/A cloning vector and the positive clones were confirmed by colony PCR with gene specific primers and restriction digestion. Phytase is a promising candidate for feed applications. The cloned gene obtained in this study will have potential for producing recombinant enzyme, which would enhance the feed quality for poultry and piggery by supplementing it in their diets.